An empirical study of implementation of EFQM method for broadcasting organization in Iran - Moluk Abbasi (Management Science Letters, 2013)
Performance measurement plays an important role on media organizations and there are literally many methods for measuring the performance of an organization. European Foundation Quality Management (EFQM) is one of the most popular methods for measuring performance of organizations. In this paper, we perform an empirical survey to customize this method for broadcasting organization of Iran. The proposed model of this paper designs a questionnaire and distributes among 3000 employees of the Iranian broadcasting organization. We have analyzed and assigned some points to different criteria and realized that standard EFQM can be considered as a customized method for taking appropriate strategies in this organization.